This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Chapter 4 Hence, a second linearly independent solution is y 2 ( t ) = t 2 Z t 6 dt ( t 2 ) 2 = t 2 Z t 2 dt = t 3 . One can also take y 2 ( t ) = t 3 , because the given equation is linear and homogeneous. 48. Putting the equation in standard form yields p ( t ) = t 1 2. Hence, exp Z p ( t ) dt = exp Z ( 2 t 1 ) dt = e 2 t ln t = t 1 e 2 t . Therefore, by Theorem 8, a second linearly independent solution is y 2 ( t ) = e t Z t 1 e 2 t ( e t ) 2 dt = e t Z t 1 dt = e t ln t. 50. Separation variables in (16) yields w w = 2 y 1 + py 1 y 1 = 2 y 1 y 1 + p . Integrating, we obtain Z w w dt = Z 2 y 1 y 1 + p dt = 2 Z y 1 y 1 dt Z pdt ln  w  = 2 ln  y 1   Z pdt  w  = y 2 1 exp Z pdt . Obviously, w ( t ) does not change its sign on I (the righthand side does not vanish on I ). Without loss of generality, we can assume that w > 0 on I and so v = w = y 2 1 exp Z pdt v = Z exp R pdt y 2 1 dt y 2 = y 1 v = y 1 Z exp R pdt y 2 1 dt. 52. For y ( t ) = v ( t ) f ( t ) = tv ( t ), we find y = tv + v , y 00 = tv 00 + 2 v , y 000 = tv 000 + 3 v 00 . Substituting y and its derivatives into the given equation, we get t ( tv 000 + 3 v 00 ) + (1 t ) ( tv 00 + 2 v ) + t ( tv + v ) tv 156 Exercises 4.8 = t 2 v 000 ( t 2 4 t ) v 00 + ( t 2 2 t + 2) v = 0 . Hence, denoting v = w (so that v 00 = w and v 000 = w 00 ) yields t 2 w 00 ( t 2 4 t ) w + ( t 2 2 t + 2) w = 0 , which is a second order linear homogeneous equation in w ....
View Full
Document
 Spring '08
 MAZMANI
 Equations

Click to edit the document details